DOI: 10.14264/uql.2015.233
|View full text |Cite
|
Sign up to set email alerts
|

Travel risk perceptions, travel intentions and influencing factors: A natural disaster context

Abstract: While studies of tourist risk perceptions and travel intentions have focused on terrorism, political instability, and outbreak diseases, limited studies have focused on natural disasters, despite the increased impact of disasters. Such events not only cause physical devastation to a tourist destination, but can affect future travel to the effected destination. Natural disasters can create risks for potential tourists which may influence their travel intentions. Thus understanding these risks and how they influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 292 publications
0
11
0
Order By: Relevance
“…In the economic field, the concept of risk was introduced in the 1920s where a decision-making study was under economic and financial areas (Hashim et al, 2018). Bauer (1960) was the first to identify risk perception in the context of consumer behavior within the marketing discipline (Lenggogeni, 2015). Then, the idea of risk has become a standard inventory of consumer behavior literature (Pike & Ryan, 2004).…”
Section: Risk Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the economic field, the concept of risk was introduced in the 1920s where a decision-making study was under economic and financial areas (Hashim et al, 2018). Bauer (1960) was the first to identify risk perception in the context of consumer behavior within the marketing discipline (Lenggogeni, 2015). Then, the idea of risk has become a standard inventory of consumer behavior literature (Pike & Ryan, 2004).…”
Section: Risk Perceptionmentioning
confidence: 99%
“…He emphasized that risk perception plays a certain role in raising the awareness of tourists on the consequences of loss. Meanwhile, Lenggogeni (2015) classified the dimensions into four different sets: time loss, hazard loss, money loss, and ego loss. Then, another study, Kaplan et al (1974) proposed five dimensions of risk perception including performance, financial, psychological, physical and social.…”
Section: Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although health and disaster most likely to sharpen tourist's travel risks for vulnerable traveler [3,28,29], our study reveal that travelling was identified as an activity that stimulate the positive emotions and support to improve traveller's mental health issue. This show that travelling shape tourist's positive emotion such as in a short vacation [20,30].…”
Section: Conclusion Implication and Future Studymentioning
confidence: 83%
“…Most tourism studies are exploratory-based research papers in nature (i.e., Devianto, Ridho, Maryati, & Lenggogeni, 2019;Filimonau & Mika, 2019;Mason, Augustyn, & Seakhoa-King, 2010;Nunkoo & Ramkissoon, 2011). There are many development research theories, such as a new scale development in tourism study (for instance, Lenggogeni, Ritchie, & Slaughter, 2019), which is often applied in the complex multiple regression-based research framework (Lenggogeni, 2015;Lenggogeni & Saito, 2018).…”
Section: Structural Equation Modelling In Tourism Research and Theorymentioning
confidence: 99%